Diagnostic Yield of Fiberoptic Bronchoscopy Washings among Patients of Sputum Smear Negative Pulmonary Tuberculosis - Muhammad Nusrullah, Afeera Hamid, Muhammad Rashid, Hafiz Muhammad Taha Waqas, Abdul Rauf (Pakistan Journal of Medical & Health Sciences, 2022)
Fiberoptic bronchoscopy with bronchial washing is done for diagnosis of pulmonary tuberculosis among patients who cannot produce sputum spontaneously. Aim: To evaluate the diagnostic yield of Fiberoptic Bronchoscopy for detection of positive cases in cases of Smear negative pulmonary tuberculosis. Study Design: Cross-sectional study. Methodology: All patients (n=80) were advised NPO for 6 hours before carrying out the procedure. It was done using local anesthesia while retrievement of the instilled amount by 25% was considered successful. The bronchial washings were sent for AFB staining in-order to confirm the presence or absence of Mycobacterium Tuberculosis. Bronchial washing smear was considered positive if 1-9 AFB/HPF are seen on direct microscopy. Statistical Analysis: SPSS v.26 analyzed the data. Stratification of diagnostic yield was done with respect to age and gender. Post stratification Chi-Squire test was applied with P-value ≤0.05 was taken as significant. Results: The diagnostic yield of FOB for detection of positive cases in cases of Smear negative PTB was 57.5%. The highest diagnostic yield was seen in patients in the age group 16-32 and 49-60 years old patients i.e. 37% in both groups. For both genders diagnostic yield for FOB was 50%. However patient’s age and gender were insignificantly associated with diagnostic yield of FOB. Conclusion: It was concluded that FOB can provide a rapid and definitive diagnosis of pulmonary tuberculosis in sputum negative patients. Keywords: Diagnostic Yield, Fiberoptic Bronchoscopy, Smear Negative and Pulmonary Tuberculosis.